Green and colourful: night market’s roles in sustaining the local culture and the informal economy - Zakariya, Khalilah (2012)
The Malaysian night market is commonly regarded as an informal and temporary place where people can buy goods and food at affordable prices. Recent studies acknowledge the contributions of night market to the informal economy, as well as towards keeping local culture alive. Through examining Lorong Tuanku Abdul Rahman (Lorong TAR) night market in Kuala Lumpur as a case study, this paper expands our notions of ‘green’ and how informal public spaces encourage the sustainability of cities from the lenses of socio-culture, spatial environment and economy. A combination of methods that include close observations, interviews and mapping were used in this study. Results showed that the night market stimulates the growth of local culture through its rich and ‘colourful’ spatial characteristics, activities and products. It can support sustainability of the informal economy by being a catalyst within itself and to its adjacent business. Night market works in multiple ways: it serves as an ephemeral public space where food and street life enliven the city, it supports vendors to start and expand their businesses, and collectively it contributes to the sustainability of local culture. These ‘green’ roles of night market should be reconsidered in planning and designing of cities for its cultural and economic contribution, rather than seeing it as ‘just another everyday space’.